A preliminary study on engineering students learning style at UNITEN - Sidhu M.S.; Omar R.; Shahidan M.S. (2023)
In this research a study was conducted on first year mechanical engineering students at University Tenaga Nasional (UNITEN). The focus of the study was to gain the students preferred learning style (using personality questionnaire) and to design new computer aided learning (CAL) packages that employs new visualization techniques. This paper first describes some theories of learning styles followed by preliminary results of students preferred learning styles. 2010 IEEE.